Drought Index Computation Using Standardized Precipitation Index (SPI) Method for Downstream Xebanghiang Watershed, Savannakhet Provinceovince - Chanthapany, Thonghuen; SIVANPHENG , Ounla; CHOMXAYTHONG, Amphone; BOUTSAMALY, Sanxay (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Drought is a major challenge that threatens both livelihoods and food security. In Laos, drought has occurred frequently, especially during the dry season. This study aimed to analyze the frequency and severity of meteorological drought in the downstream Xebanghiang Watershed, Savannakhet Province, using the Standardized Precipitation Index (SPI). Monthly rainfall data from seven meteorological and hydrological monitoring stations were collected over a 26-year period (1998–2023). The results revealed a mixed pattern of precipitation trends. Some stations, particularly Savannakhet and Seno, experienced a high frequency of both drought and wet years, indicating increased vulnerability to extreme weather events. This variability poses significant challenges for water resource management and agricultural planning. In Savannakhet, the alternating pattern of drought and wet years highlights the need for adaptive water storage systems and resilient agricultural practices that can accommodate unpredictable water availability. Seno, with its notably frequent drought conditions, appears especially vulnerable and may require robust drought mitigation strategies, including water conservation initiatives and improvements in irrigation efficiency. In contrast, Lahanam exhibited a more moderate rainfall pattern; however, occasional wet years suggest the potential for capturing surplus water to support periods of low precipitation. This SPI-based assessment emphasizes the importance of site-specific water management strategies across the watershed. Areas prone to frequent drought, such as Seno, would benefit from drought-resistant crops and community-led water conservation efforts. Meanwhile, regions with above-average rainfall should focus on harvesting and storing excess water to build resilience against future droughts. These findings provide a foundation for developing sustainable drought preparedness and water resource management frameworks to safeguard agriculture and water availability in the face of changing precipitation patterns.